Strategy survey 2022 the annual assessment of geopolitics (Strategic survey, 2022)
Strategic Survey 2022: The Annual Assessment of Geopolitics provides objective, in-depth analysis of the events that have shaped relations between major powers, region by region, over the past year, and highlights the pressing geopolitical and geo-economic challenges that will shape the international agenda in 2023. It features essays on global issues such as Russia's war in Ukraine, the arms race in space and the deepening US-China rivalry, as well as in-depth analysis of the major themes shaping each continent. Specially commissioned maps and graphics illustrate major arguments, and multi-source data illuminates longer-term trends in power relations.